Self-regulated behaviour in the akhlaq of students towards academic performance : a study on KOED undergraduates - Muhammad Izzuddin Abd Manaf (Kulliyyah of Education, International Islamic university Malaysia, 2021)
Nowadays, self-regulation can be seen as the demanding aspect in enhancing the students’ performance while at the same time, the education also should concern on the cultivation of excellent characters among the students. This study aimed to investigate the relationship between akhlaq self-regulation and academic performance among undergraduate students in International Islamic University Malaysia (IIUM). This study employed a quantitative approach which is correlation design. The sample of the study consisted of 273 undergraduates’ students from Kulliyyah of Education at IIUM Gombak. Quota sampling was used to collect the data and the SPSS software was used in order to analysed the data. The results from this study revealed that majority of KOED undergraduates had a high level of akhlaq self-regulation. Furthermore, the results also showed that the students had a high level of academic performance in term of passive performance. Meanwhile, there was significant difference in akhlaq self-regulation based on gender which implied that the female students possess higher akhlaq self-regulation as compared to male students. Finally, this study revealed that there was significant positive relationship between the level of akhlaq self-regulation and students’ academic performance. The study concludes that the akhlaq self-regulation can promote the excellence in academic performance among the KOED undergraduate students. Even so, there are some parts in akhlaq self-regulation that can be improved and should be taken into consideration for the betterment of students which mostly involved with the personal and social affairs ا